The Bontang City Library and Archives Department's Strategy to Increase Public Interest in Reading - Hapidah, Hapidah; Irawan, Bambang; Saipul, Saipul (Universitas Pancasakti, 2025)
This study explores the strategic initiatives of the Bontang City Library and Archives Department in promoting reading interest, the challenges faced during program implementation, and the evaluation of their effectiveness through the lens of New Public Service (NPS) values. Using a qualitative descriptive research method, data were collected through interviews, document analysis, and field observations to uncover the dynamics of public literacy programs. The findings reveal that the library’s innovative strategies—such as digital literacy initiatives, community reading campaigns, and partnerships with educational institutions—have contributed to improving public engagement with reading. However, these initiatives face constraints including limited funding, insufficient infrastructure, and cultural resistance to literacy practices. Evaluating the programs through NPS values emphasizes that effectiveness should not be judged merely by quantitative success but by the degree to which programs uphold inclusivity, participation, and accountability. The study concludes that sustainable literacy promotion depends on integrating strategic innovation with ethical public service values, fostering collaborative governance, and empowering citizens as active co-creators of a literate society.